The Natural Durability and Drying Properties of Ganitri Wood (Elaeocarpus sphaericus Schum) - Trisna Priadi; Arizal Sani (Wood Research Journal, 2016)
Ganitri (Elaeocarpus sphaericus Schum.) is a fast-growing species that was majority planted in community-based forets in Java. This research aimed to evaluate the natural durability and drying properties of ganitri wood, hence the best uses of the wood can be achieved. The wood durability was tested in laboratory and field scales based on SNI 7207:2014  and ASTM D 1758-02 standards respectively, while the wood treatibilty evaluation used soaking method with 5% borax preservative. The wood drying property was assessed through oven drying at 100°C temperature based on Terazawa method. The resistance of the wood against subterranean termites Coptotermes curvignathus is classified as durability class IV. Ganitri wood was very easy to be preserved with the cold soaking method.  Boron retention in ganitri was 22.87 kg.m-³, while its penetration was 27.80 mm or 94.24%. Ganitri had rather poor drying properties, which was prone to surface check. The proper drying for ganitri wood was suggested using initial and final temperatures 53°C and 83°C, respectively, while the initial and final relative humidity were 85% and 30%.